2002
DOI: 10.1063/1.1485127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of complete chaos synchronization in semiconductor lasers

Abstract: We experimentally demonstrate the complete synchronization of a semiconductor laser to the injection of a chaotic oscillating optical signal that is generated by a similar semiconductor laser with external optical feedback. The synchronization is characterized by sensitive dependencies on frequency detuning and injection strength and a time lag that varies reversely with the variation of the delay time in the external optical feedback of the master laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 17 publications
0
57
0
Order By: Relevance
“…The solution y(t) = x(t + τ ), which characterizes the anticipated synchronization (AS), has been shown to be stable in a variety of scenarios, including theoretical studies of autonomous chaotic systems [2][3][4], inertial ratchets [5], and delayed-coupled maps [6], as well as experimental observations in lasers [7,8] or electronic circuits [9].…”
Section: ) Y = F (Y(t)) + K[x(t) − Y(t − T D )]mentioning
confidence: 99%
“…The solution y(t) = x(t + τ ), which characterizes the anticipated synchronization (AS), has been shown to be stable in a variety of scenarios, including theoretical studies of autonomous chaotic systems [2][3][4], inertial ratchets [5], and delayed-coupled maps [6], as well as experimental observations in lasers [7,8] or electronic circuits [9].…”
Section: ) Y = F (Y(t)) + K[x(t) − Y(t − T D )]mentioning
confidence: 99%
“…This regime and its stability has been theoretically studied in several systems, from the simplest ones described by linear differential equations and maps where the mathematical details can be fully worked out [4,5], to the more complicated ones such as semiconductor lasers [6] operating in the chaotic regime. Experimental evidence of anticipating synchronization has been shown in Chua circuits [7] and in semiconductor lasers with optical feedback [8].…”
mentioning
confidence: 99%
“…The parameters in the two laser systems must be identical to satisfy the conditions for complete chaos synchronization, however, there are certain ranges of tolerances for the parameter mismatches when we allow a little deterioration of the correlation between the transmitter and receiver outputs. Usually, it is not easy to achieve complete chaos synchronization in real laser systems, especially in delay optical feedback systems, and a few experimental studies for complete chaos synchronization have been reported (Liu et al 2002).…”
Section: Complete Chaos Synchronizationmentioning
confidence: 99%